Research on the cultivation path of innovative and entrepreneurial talents in artificial intelligence colleges of Chongqing universities under the background of new quality productivity - Wu Yang (ITM Web of Conferences, 2025)
The innovative and entrepreneurial talents cultivated by the School of Artificial Intelligence in universities not only contribute to providing talent and intellectual support for Chongqing's development of new-quality productivity, enhancing the ability of education-strengthened cities to serve societal and livelihood improvements, but also aid in advancing the construction of the New Western Land-Sea Corridor, supporting the creation of the "33618" modern manufacturing cluster system, and optimizing the overall framework of "1361" for Digital Chongqing. Based on the analysis of the policy environment, supporting strategies, and other conditions in the process of developing new-quality productivity in Chongqing, combined with the investigation of the construction of new artificial intelligence colleges in Chongqing's universities, it is of great significance to explore and propose a cultivation path for innovative and entrepreneurial talents.